Geochemical heterogeneity of south Alpine subcontinental lithosphere: Mantle xenoliths evidence - GASPERINI D; BOSCH D; BRAGA R; BONDI M; MORTEN L.; MACERA, PATRIZIA (2004)
The Tertiary Veneto Volcanic Province (VVP; SE Alps, northern Italy) includes Na-rich alkali basalts and basanites hosting many spl-peridotite xenoliths (mg>88) among the ultramafic nodules which reflect a variably depleted mantle source [e.g. strong Cr/(Cr+Al) ratio increase at a slight Mg/(Mg+Fe2+) ratio decrease in spinels] subsequently enriched by different metasomatic processes (e.g. presence of spongy clinopyroxenes; large range of enrichment in LREE, K, Rb, Sr, and P over HREE and HFSE). New geochemical and isotopic (Sr, Nd, Pb, O) data on VVP whole rock xenoliths help evaluating the nature of the geochemical enrichment recorded in the south Alpine subcontinental lithosphere. Compared to various representative world-wide ultramafic xenoliths, the VVP xenoliths show geochemical similarities to those carried by alkaline basalts in tectonic settings dominated by the presence of hot spot magmatism (e.g. Canary and Kerguelen Islands, French Massif Central, Rhon, Eifel). Moreover, most of the enriched xenoliths display significant positive Nb and Ta anomalies, incompatible element ratios, and Sr-Nd-Pb and -O isotopic compositions similar to the host VVP alkaline basalts, thus with a marked OIB-HIMU signature. By contrast, among different agents proposed so-far to explain trace element enrichment in the VVP xenoliths, carbonatite-induced metasomatism does not appear as significantly responsible. Most of the depleted xenoliths are overall characterized by incompatible element patterns (e.g. troughs at Ba, Nb, and Ta) and ratios (e.g. high Rb/Nb, La/Nb, Th/Yb) likely related to a sedimentary component in their source, thus showing Sr-NdPb-O isotopic compositions falling between the field of MORB and altered oceanic crust ± pelagic sediments. Similar features have been observed for ultramafic xenoliths collected in basalts from subduction-related environments (e.g. Marianas, Philippines, and Papua Nuova Guinea). Lack of significant presence of hydrous phases (phlogopite, amphibole) in the spl-peridotite ...